Capturing the real‐world benefit of residual β‐cell function during clinically important time‐periods in established Type 1 diabetes. Issue 5 (10th March 2022) - Taylor, Guy S.; Shaw, Andy C.; Smith, Kieran; Wason, James; McDonald, Timothy J.; Oram, Richard A.; Stevenson, Emma; Shaw, James A. M.; West, Daniel J.
Abstract: Aims: Many individuals with type 1 diabetes retain residual β‐cell function, with increased endogenous insulin secretion associated with reduced hyperglycaemia, hypoglycaemia and glycaemic variability. However, it is unknown when these improvements occur during the day. Dysglycaemia is common in overnight and postprandial periods and associated with diabetes complications. Therefore, this study aimed to determine the influence of residual β‐cell function upon nocturnal and postprandial glycaemic control in established type 1 diabetes. Methods: Under free‐living conditions, 66 participants wore a blinded continuous glucose monitor (CGM), kept a food diary, and completed a stimulated urine C‐peptide creatinine (UCPCR) test. Nocturnal, and postprandial CGM outcomes (participant means and discrete event analysis) were compared between UCPCR groups: undetectable (Cpepund ), low (Cpeplow : 0.001–0.19 nmol/mmol) and high (Cpephigh : ≥0.2 nmol/mmol). Results: Greater β‐cell function was associated with incremental improvements in glycaemia. Cpephigh spent significantly greater time in normoglycaemia than Cpepund overnight (76 ± 20% vs. 58 ± 20%, p = 0.005) and 0–300 mins postprandially (68 ± 22% vs. 51 ± 22%, p = 0.045), while also having reducing nocturnal variability (SD 1.12 ± 0.41 vs. 1.52 ± 0.43 mmol/L, p = 0.010). Analysis of individual events, controlling for diabetes duration, BMI, basal insulin, use of a continuous or flash glucose monitor and (for postprandial) meal type, carbohydrate and bolus insulin intake, replicated the group findings, additionally demonstrating Cpepund had increased hyperglycaemia versus Cpeplow overnight and increased postprandial hypoglycaemic events compared with Cpephigh . For all participants, breakfast had a significantly higher incremental area under the curve than lunch and dinner. Conclusions: Residual β‐cell function is associated with improved nocturnal and postprandial glycaemic control. These data may be of clinical importance for identifying specific periods and individuals where further glycaemic management strategies would be beneficial.